Analisis Tingkat Kesehatan PT Bank Jabar Banten Syariah Periode 2017-2021 dengan Metode Camels, RGEC dan Alman Z-Score - Nur Azlina; Muhammad Nadratuzzaman Hosen (-, 2022)
The purpose of this study was to analyze the level of soundness of one of the Islamic banks in Indonesia, namely Bank BJB Syariah. This research is a descriptive research with a quantitative approach. The data used is secondary data obtained from literature studies, journals, internet and other literature related to research. The quantitative data in this study is the BJB Syariah financial report obtained from the Bank's annual report on its official website. The analytical technique used is the CAMELS, RGEC and Altman Z-Score methods. The overall results of the study show that the BJB Syariah Bank Soundness Level which was studied using the CAMELS, RGEC and Altman Z-Score methods resulted in a very healthy rating for the CAMELS assessment and healthy and fairly healthy for the RGEC assessment, as well as an unhealthy rating on the Altman Z-Score assessment. These three methods are relevant to be used to analyze the soundness of Islamic banks. The condition of a good health level at Bank BJB Syariah shows an unstable management performance in mitigating risk. It can be concluded that BJB sharia tends to go bankrupt. By continuing to prioritize prudential principles and good strategic management, the choice in the productive underprivileged segment is expected to provide resilience and improve finances for the Bank, and can provide wider benefits to the community, especially for Indonesian MSMEs that are more resilient as economic drivers nation.